2014
DOI: 10.1371/journal.pone.0108523
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Distribution in the Lungs of Children with Protracted Bacterial Bronchitis

Abstract: ObjectivesFlexible bronchoscopy with bronchoalveolar lavage (FB-BAL) is increasingly used for the microbiological confirmation of protracted bacterial bronchitis (PBB) in children with a chronic wet cough. At our centre, when performing FB-BAL for microbiological diagnosis we sample 6 lobes (including lingula) as this is known to increase the rate of culture positive procedures in children with cystic fibrosis. We investigated if this is also the case in children with PBB.MethodsWe undertook a retrospective ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 14 publications
1
39
0
3
Order By: Relevance
“…The distribution of bacteria within the lungs is not uniform. One retrospective study reported that sampling from a single lobe would have missed 17 different organisms in 15 out of 50 patients, eight of whom would not have had any organisms cultured [50]. Nonetheless, it should be noted that this study used nonquantitative bacterial culture methods and failed to report bacterial densities between the various lobes.…”
Section: Pbb (Kq3)mentioning
confidence: 89%
See 2 more Smart Citations
“…The distribution of bacteria within the lungs is not uniform. One retrospective study reported that sampling from a single lobe would have missed 17 different organisms in 15 out of 50 patients, eight of whom would not have had any organisms cultured [50]. Nonetheless, it should be noted that this study used nonquantitative bacterial culture methods and failed to report bacterial densities between the various lobes.…”
Section: Pbb (Kq3)mentioning
confidence: 89%
“…pneumoniae isolates in BAL cultures from fully vaccinated children with PBB in the UK were vaccine-type serotypes [51]. Finally, polymicrobial infections involving multiple respiratory bacterial pathogens were identified in the lower airways of 30-50% of affected children [16,42,[50][51][52].…”
Section: Pbb (Kq3)mentioning
confidence: 97%
See 1 more Smart Citation
“…3 Çocuklardan balgam örneğinin alınmasındaki zorluklara bağlı uzamış bakteriyel bronşitin mikrobiyolojik olarak kanıtlanması zordur, bu nedenle de hastalığın tanı ve tedavisi gecikebilmektedir. 4 Hastalığın tanısının gecikmesi solunum yollarında yapısal hasara yol açmakta ve semptomların uzamasına neden olmaktadır. 5 Tanıda altın standart bronkoskopi ile bronkoalveolar lavaj örneği alın-masıdır.…”
unclassified
“…First, antibiotic exposure at the time of sampling may suppress colony counts to below the threshold to be classified as 'infection'; second, inadequate bronchoalveolar lavage technique with poor return or very localised sampling may miss the infected portion of the lung [86]; and third, sub-optimal sample handling e.g. a delay in processing, inadequate storage, plating etc may result in failure to culture an organism that may be present.…”
Section: Bacterial Infectionmentioning
confidence: 99%